Improvement of Learning to Write Poetry Through Cooperative Learning in Middle School - Aslinda Hadi Setiana (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2022)
The general research objective in this research is to improve learning to write poetry through cooperative learning in seventh grade students of SMPN 2 Sungai Raya. The study used quantitative descriptive research with a classroom action research approach (CAR). The subjects in this study were seventh grades tudents of SMPN 2 Sungai Raya, totaling 28 students. At the time of learning, the students still lacked understanding and had difficulty composing poetry to increase knowledge during the pre-cycle among 28 students only 15 students passed the test with a percentage of 53%, continued to cycle 1, 22 students passed with a percentage of 78%, and continued in cycle II with improved planning and implementation accurately and on target using the cooperative learning model, it can only be said that 26 students passed students from 28 students with a percentage of 92%, with the Cooperative Learning model, the learning is easier to follow by students because there are smaller and more effective groupings if there are difficulties for students during learning.